2018
DOI: 10.1007/s00404-018-4769-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of Pentraxin 3 differ significantly at the time of blastocyst transfer depending on implantation success: a pilot study

Abstract: PTX3 could present as a possible biomarker for ART success. The main limitation of this pilot study is its small sample size that needs validation with a larger study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The commonly used physiological upper limit (2.0 µg/L) for circulating PTX3 is based on cardiovascular studies including both female and male elderly study subjects [10,41]. However, in later studies with healthy, normal-weight, fertile Caucasian women, PTX3 concentrations have been 1.0 µg/L or less [29,32,33]. PTX3 levels may increase by age [18,42] and obesity [43].…”
Section: The Physiological Level Of Ptx3 In Infertile Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used physiological upper limit (2.0 µg/L) for circulating PTX3 is based on cardiovascular studies including both female and male elderly study subjects [10,41]. However, in later studies with healthy, normal-weight, fertile Caucasian women, PTX3 concentrations have been 1.0 µg/L or less [29,32,33]. PTX3 levels may increase by age [18,42] and obesity [43].…”
Section: The Physiological Level Of Ptx3 In Infertile Womenmentioning
confidence: 99%
“…One small study has shown unchanged PTX3 concentration between the start of an antagonist IVF cycle and oocyte pick-up (OPU) [28]. In addition, systemic PTX3 level at the time of blastocyst transfer has been indicated as a possible biomarker for IVF success [29].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher PTX3 levels were observed in women after vaginal birth vs. caesarean section (11) . Significantly elevated maternal serum levels of PTX3 during in vitro embryo transfer have negative effects on embryo implantation (12) . Elevated blood PTX3 in the first trimester and in placental tissues is also associated with recurrent pregnancy loss (13,14) .…”
Section: Diagnosis Of Fertility Disorders and Pregnancy Pathologymentioning
confidence: 99%
“…Pentraxin-3 (PTX-3) is an acute-phase reactant and a member of the pentraxin protein family [13]. Several studies have demonstrated that PTX-3 has an important role in innate immunity, inflammation, implantation, decidualization, and placentation [14,15,16]. It has been determined that PTX-3 is expressed in the receptive endometrium, and trophoblasts have been found to affect PTX-expression in decidua [17].…”
Section: Introductionmentioning
confidence: 99%